Environmental science : - Wright, Richard T. (Pearson Education, 2014)
This edition is even more student-friendly while retaining the currency and accuracy that has made this text a best seller. The text and media program continue to help students understand the science behind environmental issues and what they can do to build a more sustainable future, with further exploration of the hallmark core themes: Science, Sustainability, and Stewardship.